Effect of intensive blood pressure control on the prevention of white matter hyperintensity: Systematic review and meta‐analysis of randomized trials. Issue 11 (10th September 2020) - Lai, Yiwei; Jiang, Chao; Du, Xin; Sang, Caihua; Guo, Xueyuan; Bai, Rong; Tang, Ribo; Dong, Jianzeng; Ma, Changsheng
Abstract: Hypertension is an important cause of cerebral small vessel disease, especially of white matter hyperintensity (WMH). The ability of intensive blood pressure (BP) control in preventing this pathological progression remains unclear. The authors systematically searched PubMed, EMBASE, SCOPUS, and Cochrane library for publications until July 20, 2020. Studies included were clinical trials with random allocation to an antihypertensive medication against placebo, or different treatment targets. The primary outcome was intergroup differences in the change of WMH volume. A random‐effect model was applied for pooling effect measures. Subgroup analysis and meta‐regression were conducted to explore heterogeneity. Seven studies with 2693 patients were identified. Compared with the control group, patients in the intensive BP control group had a slower progression of WMH, with a pooled intergroup standard mean difference (SMD) for WMH change of −0.22 (95% CI: −0.35 −0.09, I 2 = 63%). For studies comparing intensive and standard BP target, the pooled SMD is −0.37 (95% CI:‐0.50 ‐0.24, I 2 = 0%), while the pooled SMD of studies comparing active antihypertensive medication and placebo was only −0.08 (95% CI: −0.17 0.01, I 2 = 0%). Meta‐regression analysis showed that the reduction in WMH progression is proportional to the magnitude of intensive BP control ( β = −0.028, P < .001). In conclusion, intensive BP control prevents WMH progression, and its effect is associated with the magnitude of intensive BP control.